2012
DOI: 10.2135/cropsci2012.02.0139
|View full text |Cite
|
Sign up to set email alerts
|

Selection Strategy for Sorghum Targeting Phosphorus‐limited Environments in West Africa: Analysis of Multi‐environment Experiments

Abstract: Although sorghum [Sorghum bicolor (L.) Moench] in West Africa (WA) is generally cultivated with limited or no fertilization on soils of low phosphorus availability, no assessments of the genetic variation among WA sorghum varieties for adaptation to low soil P are known. We assessed grain yields of 70 diverse sorghum genotypes under -P (no P fertilization) and +P conditions at two locations in Mali over 5 yr. Genetic variation for grain yield under -P conditions and the feasibility and necessity of sorghum var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
72
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 41 publications
16
72
0
2
Order By: Relevance
“…The latter strategy may be more realistic as different pathways or P uptakeenhancing mechanisms may benefit plant growth under low versus high P conditions, leading to different genotypes being superior in each environment. Such a crossover effect, whereby different genotypes were superior under low versus moderately P-deficient conditions, has earlier been described by Kirk et al (1998) and was recently observed for sorghum (Sorghum bicolor L. Moench) by Leiser et al (2012). Specific to rice, lowland and upland ecologies may require different plant strategies for efficient P acquisition.…”
Section: Targeting Specific Environmentsmentioning
confidence: 68%
“…The latter strategy may be more realistic as different pathways or P uptakeenhancing mechanisms may benefit plant growth under low versus high P conditions, leading to different genotypes being superior in each environment. Such a crossover effect, whereby different genotypes were superior under low versus moderately P-deficient conditions, has earlier been described by Kirk et al (1998) and was recently observed for sorghum (Sorghum bicolor L. Moench) by Leiser et al (2012). Specific to rice, lowland and upland ecologies may require different plant strategies for efficient P acquisition.…”
Section: Targeting Specific Environmentsmentioning
confidence: 68%
“…In addition, because phosphate rock fertilizer is a nonrenewable resource that is being depleted by agricultural demands, increasing fertilizer prices negatively impact agriculture, particularly for small-holder farmers in developing countries in the tropics and subtropics (Cordell et al, 2009;Sattari et al, 2012). In sorghum (Sorghum bicolor), breeding strategies for low-P adaptation have been developed based on multienvironment trials in West Africa, indicating the importance of undertaking selection in low-P soil conditions (Leiser et al, 2012a(Leiser et al, , 2012b. Therefore, developing crops with greater ability to grow and maintain satisfactory yields on soils with reduced P availability is expected to substantially improve food security worldwide.…”
mentioning
confidence: 99%
“…Leiser et al (2012) assessed grain yields of 70 diverse sorghum genotypes under ÀP (no P fertilization) and +P conditions at two locations in Mali over 5 years. Leiser et al (2012) assessed grain yields of 70 diverse sorghum genotypes under ÀP (no P fertilization) and +P conditions at two locations in Mali over 5 years.…”
Section: Sorghum In West Africamentioning
confidence: 99%